Enhancement of visible light-driven hydrogen production over zinc cadmium sulfide nanoparticles anchored on BiVO4 nanorods. (12th February 2022) - Imran, Muhammad; Yousaf, Ammar Bin; Farooq, Muhammad; Kasak, Peter
Abstract: Photocatalytic water splitting to produce H2 is a promising technology for clean energy generation. However, the use of expensive noble metals, toxicity, low charge separation efficiency and wide band gap of semiconductors hampering the widespread commercialization. Herein, we showed the potential of combining BiVO4 nanorods with ZnCdS forming a hetero-structure which extend the spectral responsive range, separate the charge carriers effectively and enhances photocatalytic activity compared to single-component materials. The two components of hetero-structure forms an interface contact which also mitigate the problems of lower conduction band position of BiVO4 and fast recombination of charge carriers of ZnCdS. The BiVO4 –ZnCdS hetero-structure was studied through surface morphology, crystallization properties, elemental analysis and optical properties. Under visible light irradiation, the BiVO4 –ZnCdS heterostructure produced 152.5 μmol g −1 h −1 hydrogen from water splitting, which was much higher than that of the individual components and stability of the hydrogen production was observed in three consecutive cycles. The as-obtained heterostructure showed improved visible light harvesting ability, prolong life of charges carriers and charge separation efficiency and Z-scheme mechanism features which results in enhanced photocatalytic activity for water splitting. Graphical abstract: Image 1 Highlights: A novel BiVO4 –ZnCdS heterostructure is introduced as photocatalyst. The developed catalyst was used for visible light driven hydrogen production. Interface among BiVO4 and ZnCdS improved photocatalytic profile of catalyst. BiVO4 –ZnCdS heterostructure produced up to 152.5 μmol g −1 h −1 hydrogen. Z-scheme mechanism enhanced the performance herein as noble-metal-free catalyst.